Computational analysis of genes encoding for molecular determinants of arsenic tolerance in rice (Oryza sativa L.) to engineer low arsenic content varieties - Das, Chinmaya Kumar; Bastia, D; Swain, S C; Mahapatra, S S (ORYZA-An International Journal of Rice, 2018)
Rice (Oryza sativa L.) stands at the centre stage of the dietary landscape as one of the principal staple food crop in the globe. Unfortunately, it is known to be a potential accumulator of toxic metalloid arsenic, a non-threshold, class 1 human carcinogen, in its grains. Therefore, it is imperative to device strategies to minimize the level of arsenic toxicity in rice grains. In this investigation, we have analyzed the transcriptional regulatory architecture of genes involved in arsenic metabolism in rice by analyzing their gene coexpression modules, their spatiotemporal expression profiles in different tissues during developmental phases of rice and scanning of their upstream promoter regions for potential transcription factor binding sites (TBFS) using computational tools & genomic/ transcriptomic data available in a set of genomic databases (RiceFREND, RiceXPro, PlantPAN2.0, RAP-DB, OryzaBase, MSU Rice Genome Annotation Project Database & Resources and NCBI) and manually written RScripts to understand the molecular basis of arsenic tolerance for designing varietal interventions with minimum arsenic toxicity. In the analysis of gene coexpression modules of candidate genes of arsenic metabolism, MYB or MYB-related TF encoding genes were enriched in the constructed gene-coexpression network of one candidate gene OsHAC1;1 which encodes for an arsenate reductase enzyme in rice. Further, potential TBFS of MYB were found on the upstream promoter region of OsHAC1; 1 gene. Upregulated and downregulated gene expression pattern of both OsMYB48 (A P-type R2R3 MYB transcription factor) and OsHAC1;1 in root tissues and most of the reproductive structures (inflorescences, anthers, pistils, ovaries, embryos and endosperms), respectively were found in the spatiotemporal analysis of gene expression . Therefore, contrasting differential gene expression pattern of both OsMYB48 and OsHAC1;1 genes in root and reproductive organs has a potential significance in restricting toxic arsenites in the cellular vacuoles of root tissues with canonical ABC transporter (OsABCC1) at vegetative and reproductive stages and thereby limiting the translocation of toxic As into the grains. Hence, functional validation of OsMYB48 mediated transcriptional modulation of OsHAC1; 1 gene in the root and reproductive tissues would help in gaining insights into the basis of arsenic tolerance in rice and designing genetic strategies for evolving low grain-arsenic content varieties of paddy using genetic engineering and plant breeding tools.